A Retrospective Cohort Study of Glossopharyngeal Nerve Taste in Children with Recurrent Acute Tonsillitis. (25th October 2016) - Hill, Courtney A.; Dang, Suveera; Beach, Michael; Chen, Eunice Y.
Abstract : Objective: To compare glossopharyngeal taste between healthy children and those with recurrent acute tonsillitis. Study Design: Retrospective cohort study. Setting: Pediatric clinics in a tertiary care medical center and satellite location. Subjects and Methods: Smell and taste testing was administered to 80 well children and 64 children with recurrent acute tonsillitis (age range, 6‐17 years). Smell testing was performed with the NIH Toolbox Odor Identification Test, with scores based on national averages for age and sex. Validated Taste Strips were placed on the midline of the tongue at the circumvallate papillae in random tastant order and in increasing concentrations to test sweet, salty, sour, and bitter. Ordinal logistic regression was used for multivariate analysis. Results: The healthy and tonsillitis groups were similar, with mean ages of 11.3 and 10.8 years ( P =. 34), respectively. The tonsillitis group had fewer boys (n = 18 vs 43, P =. 002), higher mean body mass index (BMI) percentile (n = 72.2 vs 59.8, P =. 01), and more subjects with public or no insurance (n = 24 vs 13, P =. 004). Univariate analysis revealed no statistically significant differences in rate of normal overall taste (67.2% vs 60%, P =. 39) and in sweet (79.7% vs 82.5%, P =. 67), salty (85.9% vs 82.8%, P =. 82), sour (64.1% vs 70%, P =. 48), and bitter (90.6% vs 86.3%, P =. 45). In multivariate analysis, smell ability, sex, BMI percentile, parent BMI, and insurance type did not affect overall taste or sweet, salty, sour, or bitter alone. Conclusion: Despite controlling for potential intrinsic (sex, smell, BMI) and extrinsic (parent BMI, insurance type) confounders, there was no statistically significant difference in taste among children with recurrent acute tonsillitis as compared with healthy children.